Determinan Persepsi Mahasiswa Akuntansi Mengenai Etika Atas Penggelapan Pajak (Tax Evasion) (Studi Empiris pada Mahasiswa Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Abet Alfarizi; Moh. Amin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to analyze the influence of several determining factors on the perceptions of accounting students regarding the ethics of tax evasion, namely fairness, discrimination, and the tax system. Tax evasion is an unlawful act carried out by taxpayers who aim to reduce the amount of tax charged or make efforts not to pay taxes illegally. This study uses primary data with the criteria of students majoring in accounting at the Faculty of Economics and Business, Islamic University of Malang who have taken taxation courses. The research was conducted using data collection methods through questionnaires with google form media using a Likert scale of 1-4. In determining the sample the researcher used the slovin formula so that the number of samples used in this study was 87 students, using the data analysis method of multiple linear regression analysis. The results of the research test prove that fairness, discrimination, and the tax system have a positive and significant effect on the perceptions of accounting students regarding the ethics of tax evasion. Keywords: Tax evasion, fairness, discrimination, tax system